Leaching of copper slags by direct photooxidation mechanism using ultraviolet light - Sari, Zeynel Abidin; Turan, M. Deniz (Journal of Central South Univ, 2024)
The dissolution behaviors of Cu and Fe from copper slags were investigated with photochemical reactions. Experiments were run intermittently with a quartz glass jacket in a glass reactor, by submerging ultraviolet (UV) lamps and using glass tube as an air supply distributed under the reactor. The behaviors of UVA (365 nm), UVB (311 nm), UVC (254 nm), and vacuum-UV (VUV) (185 nm) light at different wavelengths in a leaching solution were examined. All experiments were conducted comparatively in the presence and absence of UV lamps under identical conditions. The adaptation of the radical formation mechanism to the leaching environment and its usability in leaching by creating an oxidative solution medium were investigated. In the experiments in the UV light (185 nm) and non-UV light environments under optimum conditions, the copper extraction rates were obtained as 85.1% and 70.7%, respectively. In conclusion, the metal dissolution (Cu) behaviors at optimum conditions during leaching from copper slags in the photoreactor systems with UV (185 nm) light were more efficient than those without UV light. Moreover, photochemical reactor is a new approach to adapt them to hydrometallurgy applications and examine the process. ??????????????Cu?Fe????????????????, ?????? ????, ???????????, ???????????????????UVA (365 nm)? UVB (311 nm)?UVC (254 nm)???UV?(185 nm)??????????????????, ? ???????????????????????????????????????????? ????????????(185 nm)????????, ????????85.1%?70.7%???? ?, ???(185 nm)??????, ??????????????????????????? ?????????????????????????????
Keywords: leaching; copper slags; photochemical oxidation; ultraviolet lamp; oxidative radical; ??; ???; ?????; ????; ?????